Attraction and Repulsion in the Arab Novel in Iraq After 2003 AD, A Study in Light of the Data of the Great Zero - Ibraheem, Iqbal Ahmed Abdul Hussein; Mahdi, Eman Mutter (Journal of Ecohumanism, 2024)
The Arabic novel occupies, today in the cultural and intellectual present, an important space in which a set of adjacent issues intersect, which continue to accompany the process of formation and development of this problematic literary genre, which has not ceased to generate questions based on the mechanisms of internal development, and the main variables that affect the components and function, and give legitimacy to the creation of new forms and patterns. The novel is no longer topics that talk about love or tragedy and comedy, but has become an exploration of the secrets of the human soul that have not been addressed before, and a dive into its depths in search of a truth deeper than the external truth of events, things and phenomena familiar to the external sense.